P–255 Hyaluronic acid-sperm selection significantly improves the clinical outcome of couples with previous ICSI cycles failure. (6th August 2021) - Scaruffi, P; Bovis, F; Casciano, I; Maccarini, E; Leo, C D; Massarotti, C; Sozzi, F; Stigliani, S; Anserini, P
Abstract: Study question: Does hyaluronic acid (HA) sperm selection improve the intracytoplasmic sperm injection outcome of couples with previous ICSI cycles failure? Summary answer: In couples where previous first ICSI failed, selection of HA-bound spermatozoa significantly improved clinical outcomes respect to further standard ICSI. What is known already: HA is the major component of the matrix surrounding the human oocyte and in physiological fertilization it plays an important role in sperm selection since only mature spermatozoa express specific binding protein and are able to bind to HA. Although several studies demonstrated better outcomes of ICSI with selection of mature HA-bound spermatozoa, such a beneficial effect of HA-ICSI is still controversial and to date no firm clinical guidance for the routine use of HA can be drawn. Further studies are needed to categorize patients that really might benefit from HA sperm selection before ICSI. Study design, size, duration: A retrospective, longitudinal cohort study performed at a tertiary level public infertility center. We selected 164 couples who performed one or more failed ICSI cycles with low fertilization rate and poor embryo quality in the period 2010–2020 (n = 164 cycles, group A), followed by other standard ICSI (n = 99, group B) and/or HA-ICSI (n = 96 group C) cycles. We included only fresh ejaculated sperm and fresh oocytes. Participants/materials, setting, methods: Endpoints were fertilization, cleavage, top quality embryo, implantation (IR), clinical pregnancy (CPR), pregnancy loss (PLR), and live birth (LBR) rates. Comparisons among groups were performed using a generalized estimating equation model performed at patient level, to take into account the correlation between observations originating from the same woman. A p-value <0.05, after correction by female age at oocyte retrieval, was considered statistically significant. Main results and the role of chance: The three groups were similar for number of retrieved, MII and injected oocytes. As regarding embryological outcomes, there was no difference in fertilization and cleavage rates between group A and C (fertilization: 47.55 + 29.88% versus 54.10 + 28.51%, p = 0.096; cleavage: 96.19 + 12.70% versus 97.52 + 10.50%, p = 0.519), nor between group B and C (fertilization: 60.30 + 30.73% versus 53.71 + 28.61%, p = 0.112; cleavage: 92.26 + 20.540% versus 97.55 + 10.44%, p = 0.106). Selection of HA-bound spermatozoa in ICSI significantly improved the embryo quality rate (63.78 + 35.55% versus 51.42 + 34.31% p = 0.024) and the blastulation rate (43.44 + 25.55% versus 17.93 + 25.52%, p = 0.001) respect to standard ICSI. Comparisons of clinical outcomes between group B and group C highlighted significant higher IR (26.16 + 40.47% versus 7.34 + 22.16%, p = 0.0001), CPR/cycle (32.29% (31/96) versus 12.12% (12/99), p = 0.0007, chi-square test), and lower PLR (12.90% (4/31) versus 41.67% (5/12), p = 0.0398, chi-square test) in HA-ICSI respect to standard ICSI cycles. The LBR/cycle in group B was 10.10% (10/99) and in group C was 32.29% (31/96) (p = 0.0029, chi-square test). No stillbirths as well as no malformations in newborns were recorded. Limitations, reasons for caution: We are aware of the retrospective nature of the study performed in a single ART center. Wider implications of the findings: This study identified couples with previous ICSI cycles failure as a category of infertile patients that really may benefit from HA sperm selection before ICSI. Trial registration number: Not applicable